Стигматизацијата на лица со нарушено ментално здравје и контактите со нив кај студенти со различна професионална ориентација - Поповски, Михајло; Наумова, Катерина (Филозофски факултет, Скопје, 2015)
The paper presents results from a study on the features of stigmatization of people with various mental health disorders - schizophrenia, drug and alcohol addiction and its relationship with the number and closeness of contacts established with them. The participants in the study were two groups of students with different professional orientation: the first group is composed of students who are being educated for professions that are primarily oriented towards helping people, while the second group is composed of students who are educated for other professions. Data were collected with the Attribution Questionnaire-27 and the Level of Familiarity Scale. The analysis showed that both groups of students stigmatize addiction more than schizophrenia. The most salient tendency toward stigmatization and discrimination was determined in relation to drug addicts, especially in the second group of students. Comparison between the groups revealed a more pronounced readiness in the second group of students to discriminate people with schizophrenia or addicted to alcohol. Unlike them, students from the first group express increased preparedness for helping in relation to all three mental health disorders. More frequent and closer contacts with people who have mental health disorders contribute to the decline of feelings of fear and danger of them, and of the tendency for their discrimination. The findings indicate a need for appropriate anti-stigma programs that would offer better information about the nature and features of mental health disorders, thus reducing their stigmatization and discrimination.
Stigmatization of people with mental health disorders and contact with them in students with different professional orientation
Keywords: stigmatization, discrimination, mental illness